Determinants of food security indicators in Bahir Dar City, Ethiopia: a focus on female-headed households - Getenet Ewunetu Tegegne; Arega Bazezew Berlie; Demsew Mengistie; Abiy Yigzaw (Discover Sustainability)
Abstract High food prices have severely affected poor female-headed households in urban Ethiopia, particularly in Bahir Dar city, where there is limited empirical evidence regarding their food insecurity. This study aims to identify the determinants of food security among female-headed households across three sub-cities and six kebele administrations in Bahir Dar. Through key informant interviews, focus group discussions, and a structured survey of 330 households, the study employed the reduced coping strategy index (rCSI), household dietary diversity score (HDDS), and household food insecurity access scale (HFIAS) for assessment. The findings revealed that 87.9% of female-headed households were food insecure, with 86.4% relying on high coping strategies. Notably, 54% of these households were consuming fewer than three food groups, indicating significant nutritional inadequacy. According to HFIAS results, 66.7% of respondents were classified as severely food insecure. Common coping strategies included consuming street food, skipping meals, and opting for less preferred or cheaper food options. The ologit regression results showed that total income, household size, residential kebeles, and housing ownership are significant determinants of food security among female-headed households. In conclusion, the study highlights the urgent need for policymakers and government organizations to address the food insecurity challenges faced by female-headed households in Bahir Dar and similar urban areas across Ethiopia.